The Effect of Recruitment, Selection, and Commitment on the Quality of Work of PMI Volunteers in Jombang Regency - Ammelia, Lailatul Ammelia Rahmawati; Lailatus Sa’adah; Moh. Jafar Sodiq Maksum (Universitas Indo Global Mandiri, 2025)
The purpose of this research is to determine the influence of recruitment, selection, and commitment on the work quality of PMI volunteers in Jombang Regency. The method used in this research is the quantitative method. This research is used to determine whether there is an influence or relationship between the targeted variables. For the determination of the sample to be used in this research, various sampling techniques are employed. Non-probability sampling is a sampling technique that does not give equal opportunities for every element or member of the population to be selected as a sample. The population in this study consists of 50 people, and the sample also consists of 50 respondents using the saturated sampling technique. What is meant by the saturated sampling technique is a sampling method that uses the entire population as the sample. The data collection technique used was through observation and distributing questionnaires via Google Form, which were subsequently analyzed using multiple regression analysis with SPSS version 15. The research results show that there is a significant influence between recruitment and the quality of volunteer work, no significant influence between selection and the quality of volunteer work, and a significant influence between commitment and the quality of volunteer work. The result of the coefficient of determination analysis was 0.867 or 86.7%, which means the contribution of the recruitment, selection, and commitment variables to the quality of volunteer work is 86.7%, while the remaining portion is influenced by other factors outside this regression model. Keywords: commitment, work quality, recruitment, selection